Problematizing Silence in Research Involving Vulnerable Older Adults - Owasim Akram; Rebecca Baxter (International Journal of Qualitative Methods)
Millions of older people are living in extreme poverty around the world. Experience suggests that such groups of people often respond with silence in research to express their social position and lived experience of impoverishment, vulnerability, oppression, and marginalization. However, understanding the eloquence that exists within the expression of silence is an empirically neglected phenomenon in scientific research, especially in studies that engage vulnerable older adults. This article, with support from practical experience and example interviews, leans towards a decolonial position that older people living in extreme poverty form a subaltern subclass who may express their lived experience using episodes of silence. The silence of vulnerable older people in research hints at a possible explanation for their silence in politics and policy discourse. Thus, it is crucial to consider silence as an empirical and primary text to illuminate perspectives of ageing within the lived context of poverty. This article intends to inspire methodological discussion as a step towards formulating strategies to empirically address silence in qualitative research involving vulnerable older adults living in poverty.